Advances in Maize Transformation Technologies and Development of Transgenic Maize - Yadava, Pranjal; Abhishek, Alok; Singh, Reeva; Singh, Ishwar; Kaul, Tanushri; Pattanayak, Arunava; Agrawal, Pawan K. (Frontiers in Plant Science, 2017)
Maize is the principal grain crop of the world. It is also the crop where genetic engineering has been employed to a great extent to improve its various traits. The ability to transform maize is a crucial step for application of gene technology in maize improvement. There have been constant improvements in the maize transformation technologies over past several years. The choice of genotype and the explant material to initiate transformation and the different types of media to be used in various stages of tissue culture can have significant impact on the outcomes of the transformation efforts. Various methods of gene transfer, like the particle bombardment, protoplast transformation, Agrobacterium mediated, in planta transformation etc. have been tried and improved over years. Similarly, various selection systems for retrieval of the transformants have been attempted. The commercial success of maize transformation and transgenic development is unmatched by any other crop so far. Maize transformation with newer gene editing technologies is opening up a fresh dimension in transformation protocols and work-flows. This review captures the various past and recent facets in improvement in maize transformation technologies and attempts to present a comprehensive updated picture of the current state of the art of this area.